Διαδικτυακή διάλεξη από την Οικία Patrick & Joan Leigh Fermor (The Benaki Museum, 2022)
: Ευχαριστούμε πολύ, κυρίες φίλοι. Καλή φίλια, ονομάζομαι Γιώργος Μαγγίνης και είμαι ο ακαδηματικός διευθυντής του Βενάκη Μουσείου στην Αθήνα. Συμβουλευτής του Μουσείου, θα θέλαμε να σας καλωσορίζουμε στο πρώτο μοναστήριο που θα δημιουργηθεί live στο ίντερνετ από το Βενάκη Μουσείο του Πατρίκ και του Γιάννου Λύφερμα, στην Καρδαμίλη, η νεκρότερη ασφάλεια στο Βενάκη Μουσείο του Βενάκη Μουσείου. Ήταν πριν το 1996, που ο Πατρίκ και ο Γιάννου Λύφερμα διευθυντήθηκαν το λεγεντρικό σπίτι στο Βενάκη Μουσείο, με την εντυπωσία ότι η ασφάλεια των χωριών θα μεταφέρθηκε στο Βενάκη Μουσείο μετά την αγώνα. Η ασφάλεια διευθυντήθηκε για να συμβουλεύει στην ασφάλεια του Βενάκη Μουσείου, σύμφωνα με την αποτυπωσία που έγινε από το Βενάκη Μουσείο. Επίσης, ήταν το εφημεριστικό θέμα των Λύφερμαν ότι το Βενάκη Μουσείο θα χρησιμοποιηθεί για να διευθυντήσει επισκέπτες, που προσπαθούσαν για ένα χαμηλό και ασφαλικό μέρος στο οποίο να δουλεύουν. Η Βενάκη Μουσείου ανοίγε πλήρως τις εξελίξεις της ασφάλειας, καθώς και τις χρήματα όλων των χρήσεων εξελίξεων. Το Βενάκη Μουσείο ανοίγε την κοινότητα το Ωκτώβρο 2019. Από το πρώτο, τρεις ακαδημικές ιστοιτήσεις σχέθηκαν στη Βενάκη για να διευθυνθούν το θέμα των Λύφερμαν. Η UCLA, η Ευρωπαϊκή Καλifornία και το Λοσάνγελιστο, η Πρυνστινγκ Βουλή και κυρίως το Κέντρο για την Κυριακή Ελλάδα. Η τελευταία ιστοσύνη και το διευθυντής, ο διευθυντής Μίλτος Πεχλιβάνος, έχουν διευθυνθεί τελείως στις δημιουργήσεις και στις ακαδημικές σε αυτό το όμορφο κομμάτι της Ελλάδας, το Λοσάνγελιστο Λοσάνγελιστο Καρδαμίδι. Από το Ωκτώβρο 2021, ο διευθυντής Μίλτος Πεχλιβάνος οργανώθηκε ένα σεμινάριο με το όμορφο κομμάτι «Προταγωνιστές της Γερμανικής Ελληνικής Προταγωνίας». Το Κέντρο για την Κυριακή Ελλάδα ήταν επίσης ενδιαφέρον στο διευθυντή Μίλτος Πεχλιβάνος με το στόχο να διευθυνθεί μια συμφωνία στο Καρδαμίδι αυτή τη εβδομάδα. Η συμφωνία σήμερα είναι μέρος αυτής της συμφωνίας και είναι δημιουργημένη από τον διευθυντή Χαρτμούτ Λεππιν του Διευθυντή Μίλτος Πεχλιβάνου της Γερμανικής Ελληνικής Προταγωνίας. Ο διευθυντής Λεππιν διευθυνθεί στην Ευρωπαϊκή Μαρβουρντ, όπου διευθυνθεί το φιλίδι του. Ο διευθυντής του διευθυνθεί στην Ελληνική Προταγωνία το 1995. Από τότε, διευθυνθεί στην Ευρωπαϊκή Μαρβουρντ και στην Ελληνική Προταγωνία του Πάτερβουρντ και του Γράφσφαλτ. Είχε δημιουργήσει πλήρως πρωθέα της αρχαίας ιστορίας στην Ευρωπαϊκή Μαρβουρντ της Γερμανικής Προταγωνίας το 2001 και έχει διευθυνθεί πολλές εξαιρετικές, ακαδημικές θέσεις. Είναι και ο διευθυντής των πολλών μονογραφών, και διευθυντής πολλών εξοπλών και διευθυντής πολλών εξοπλών στις Κλασσικές και Ρωμανικές περίοδες, όπως και στις Αρχαίες Μετρικές. Ο διευθυντής του έχει διευθυνθεί συγκεκριμένως στην Ευρωπαϊκή Μαρβουρντ και στην Ευρωπαϊκή Μαρβουρντ. Είναι σημαντικό να συναντήσεις ένας σχολός που ανοίγει έναν τεράστιο χρονολογικό σπαν και πολλές διαφορετικές ερωτήσεις για την κοινωνία, τη δικαιοσύνη, την πολιτική, τη διευθυντή, την λιτουργία, την φιλοσοφία και άλλα διευθυντήσεις. Αυτή η διευθυντή είναι εφαρμογημένη στη διευθυντή του σύμφωνα στις ακαδημικές εργασίες, όπως το Ινστιτιτούτο του Ατμάνστατια Πρίνστον, την Ακαδημία Μπροσιανα και άλλα κομμάτια, όπου υπάρχουν διευθυντή και εφαρμογημένη σύμφωνα στις ακαδημικές εργασίες και περιοδικές. Έχει διευθυντήσει με προστιτουργικές εργασίες. Μερικές πρόσφατες, το πρόγραμμα του Geistern Wissenschaften International, το πρόγραμμα του Erwin Stein και το πρόγραμμα του Gottfried Wilhelm Leibniz. Όλοι εμείς στο Μουσείο του Βενάκης είναι ειδικά χαρούμενοι και χαρούμενοι να καλωσορίζουμε τον Πρόεδρο Λέπιν. Προσωπικά, ευχαριστώ πολύ για την εγγραφή του, για να μας μιλήσει σήμερα από την εξοπλισμία στον Πειράτο. Πειράτες στην αρχαία Ελλάδα. Πρόεδρο Λέπιν. Ευχαριστώ, Γεώργο, για την ευχαριστή σας. Πρώτα απ' όλα, θα ήθελα να ευχαριστώ στο Μουσείο του Βενάκου, το Κέντρο Μοντέρνης Κρίσινων στην Βερλίνα, για την πρόσφαση σε αυτή τη μορφή και στο Μουσείο του Βενάκου για την υπηρεσία εδώ, στο υπέροχο Λιβ Φέρμα στο Κάβαν Μιλί. Είναι έναν υπέροχο μέρος που έχει κατασκευαστεί με υπέροχη καρία και αίσθηση και είμαστε σκληρά εντυπωσμένοι από το ομάδι του Βενάκου. Κατασκευασμένοι, ευχαριστώ πολύ. Σε ευχαριστώ πολύ στον Μιλτοκαούκη, που μας βοηθήθηκε σε έναν υπέροχο τρόπο για την οργάνωση της συμμετοχής μας. Σε αυτόν τον τρόπο, η υπέροχη ελληνική παραδοσιακή της υπέροχης γίνεται αλήθεια. Είμαστε υπέροχοι από την υπέροχη σας. Σας ευχαριστούμε, γιερτιν, υπέροχοι, φιλοξενίες, σας. Είμαστε ένας μικρός σχολός από την Ελλάδα, την Αυστρία, την Σουετσαλονίκη, την Γερμανία, την Γερμανία και την Ελλάδα, από διάφορες διεξιότητες που ήρθαν στο σπίτι, για να μιλήσουμε για την ιστορία της υπέροχης, για τις δικαιωμάσεις της υπέροχης, για την παραδοσιακή της υπέροχης και της λιτουργίας. Σας ευχαριστούμε, ποιες χώρες υπέροχε την υπέροχη, ποιοι ήταν οι concept of honor της υπέροχης, αν ήταν κομμουνιστές ή αρχαίοι καπιταλιστές, για να πούμε μόνο λίγο. Όλοι οι μιλήσεις υπέροχες από αυτήν την ιστορία της υπέροχης. Δεν θα μιλήσω τώρα για να δώσω τη σκηνή μου. Πρέπει να είναι δημιουργημένη τώρα. Το λόγο pirate είναι από την Ελλάδα. Ο concept, however, developed only slowly in Greece. In any case, if one is willing to take a wide sweep, one can observe in Greek history how pirates differentiated themselves from other communities of violence and were nevertheless interchangeable with other groups of this kind. Community of violence is a clumsy translation of the German term Gewaltgemeinschaft, which defines non-institutionalized groups that are integrated by the common use of violence, independently of the justifications, be they religious, political or economic. Although in classical Greece everyone knew what to think of as a pirate, it was difficult in many cases to say whether a particular group of violent people at sea should be addressed as pirates. I will elaborate on this in the following by focusing on three constellations, Homer's World, the Attic Sea League, and the Cilician Pirate Empire. But first, as a scholar of antiquity, allow me to say a few words about the linguistic background. The Greek word for pirate is perates. I use the German pronunciation of ancient Greece, Greek. Perates, a noun technically speaking known againtus, which is derived from the verb perrao. Its basic meaning is given by dictionaries as to make an attempt. Shades of meaning can be gonna take something, to dare something, to try something, but also later in the Christian context to try someone. The noun usually simply means pirates. The basic meaning entrepreneur, however, gave the impetus for the conference planning in our case, as we study also the relationship between entrepreneurs and pirates. Later a very similar word, perastes, appeared, meaning the one who makes an attempt, thus preserving the general meaning of the verb, but especially denoting the tempter among Christians. Next to it exists the word lestes, which can denote robbers by sea as well as by land. This word is the older one. Perates only appears in the Hellenistic period, in the time after Alexander the Great, who died in 323 BC, as you know. The word katapontestes, for which there is also a corresponding verb, is the one, to translate it literally, who throws into the sea. The word is attested since the early 4th century, but much rarer than perates. The concept of the pirate as an actor who, as the analyst at sea, captured ships and took people prisoner, developed only gradually in Greece. As I said, anyone who speaks of pirates must assume that the sea is the space of a rule-based order. In antiquity, however, there was no authority that could have established, enacted, or enforced any supra-regional rules. For some, the guarantors of order between the cities were the gods, who were perceived as inner-worldly actors. Otherwise, people depended on mutual trust, which was stabilized by certain concepts of honor and statehood. Ancient Greeks often had similar ideas about these phenomena, sometimes also non-Greeks, barbarians from the Greek point of view. But these ideas were not stable and could not be enforced by humans. Thus, the concept of the pirate remained diffuse. Ancient authors remained aware of this until late antiquity. Bishop Augustine of Hippo follows Cicero in this, approvingly quoting a pirate. See the text on the presentation on the screen. Indeed, that was an apt and true reply, which was given to Alexander the Great by a pirate who had been seized. For when that king had asked the men what he meant by keeping hostile possession of the sea, he answered with bold pride, what you mean by seizing the whole earth, but because I do it with a petty ship. I am called a robber, while you who does it with a great fleet are styled king or emperor. Homer's Odyssey demonstrates the openness of the assessment of sea-borne violence very clearly at the beginning of antiquity, when Odysseus, shipwrecked, and having arrived at the Phaeacians, makes himself known, he tells what happened to him on the voyage from Troy. Quote, from Ilion the wind carried me and brought me to the Sisonese, to Ismaros. There I destroyed the city and annihilated the men. And when we had taken from the city the women and many goods, we divided them among us that none of the equal portion might be lost to me. Later Odysseus urges his companions to leave, but they prefer to celebrate. So the escaped Sisonese can summon the others and together attack the Achaeans, the Greeks who flee with great losses. What happened here was piracy in the terms of later Greeks and in ours anyway. But Odysseus tells this without reservation and boasts of his justice, if only to his companions. Internal justice is often an important theme among pirates later on. If one uses the term pirate not as a firmly delimited term, but as a bundle term containing various elements, Odysseus and his companions would be pirates insofar as they committed acts of violence from the sea out of personal economic interests. But his acts of violence did not contradict any general normative ideas in the narrative context, but only the obvious interests of the Sisonese. But there's also another phenomenon visible in this episode that can be observed time and again with real pirates, to put it this way. Their strength lies in their sudden attack. They are, however, no match for the massive power of the land dwellers. What is reported in the Odyssey is not an isolated account. Such undertakings are mentioned again and again, and in such a way that one has the impression that they were taken for granted. That, on the other hand, there was fear of the pernicious consequences of piracy is evident from other texts. This, however, did not imply dishonor on the part of the perpetrators. In the period we call archaic and scholarly terms, there was no talk of piracy in the sense that they were distinguished from other communities of violence. But at some point, this changed. We make a long jump in chronology. When the historian Thucydides writes his Peloponnesian War, his treatise on the devastating war between Athens and Sparta that broke out in 431, at the height of the Greek classical period, he also gives a historical review. There he makes the following observation. Quote, in former times, the Greeks and those barbarians who lived on the mainland on the coast or had islands, after it was easier for them to reach each other by sea, turned to piracy, and their leaders were not exactly the weakest. They did this for their own gain and to feed the needy. They raided poleis that were unfortified or consisted only of a collection of villages and plundered them. From this, they gained the greater part of their livelihood, and they attracted no disgrace at all. In fact, they gained a certain fame. Greek, as well as barbarians, engaged in piracy, and this brought them no shame, according to Thucydides. He also takes corresponding hints from the older poets, certainly also from Homer, as he explains in the following. Above all, he notes that even in his time, people in some places shared such values and appreciated pirates. Here, Thucydides obviously sees a difference to his world, where piracy damaged reputations. Unfortunately, he gives no reasons for this development. His position, however, is understandable, as that of a member of a city that regularly called its citizens to arms, but where weapons were not simply carried around openly, and which in this respect had something like a monopoly on violence. It may have been important for the development of the concept of piracy that Athens depended on safe sea routes for its grain supply, but the grain came from the Black Sea. You see the large number of islands which had to be passed. They belonged to the Attic Sea League, an alliance system that was strongly determined by Athens. In a treaty, an ally was required not to engage in piracy, and also not to allow pirates into the harbor, distinguishing them from ordinary enemies. Grain supply, on the other hand, was one of the very few economic areas in which ancient states intervened. It was a matter of elementary needs of the population. Under these circumstances, it was obviously important to distinguish between a legitimate and an illegitimate use of violence at sea. To put it this way, which is a bit anachronistic, because there's no law among people in the ancient world. Thucydides, however, does not use such terms. For him, the focus is on the prestige that someone could gain through his activity, including from piracy. He himself observes that the corresponding concepts could vary regionally, but obviously considers his, separating piracy from other forms of violence, the correct one. In any case, the distinction between respectable violent action at sea, which distinguished the Athenian fleet, and disgraceful violent action was thus established. Sadly, we are not able to grasp the developmental steps before Thucydides. Of course, the distinction in general did not mean that people agreed on the assessment of individual cases. In my opinion, a clear distinction between mercenaries and pirates, as is often populated in research, did not exist in antiquity. Piracy was to a considerable extent a question of the perspective. Allies of the enemy could be discredited as pirates. The same group could also act situationally at times as pirates or as mercenaries, depending on whether they were in the service of others or acted as freelancers, to put it that way. The invention of piracy was thus achieved in the first place by those who formed a recognized political entity and claimed the power to control the sea. One thinks back again to Augustine's pirate. Thucydides also addresses a second idea that was to become essential for dealing with pirates in antiquity. He mentions the Cretan king Minos, who is a historical figure for him. He was the first to acquire a naval power and was thus able to gain naval supremacy over the Greek sea. And of course, he eliminated piracy in the sea as far as he could in the expectation that the revenues would go to him." The formula, of course, denotes processes that can be expected, such as when it should be made plausible in court that a person was the culprit or just not. Thus, if someone gained naval supremacy, it was to be expected that he would eliminate piracy, if only out of sheer self-interest. Conversely, this meant that whoever eliminated the pirates also had to be recognized as the ruler of the sea. Obviously, this was not a matter of formalized legal status, but a sign of success and an object of glory. In practical terms, the economically increasingly interconnected ancient powers depended on the sea being as safe as possible. The dangers of nature were threatening enough. The question becomes more acute after the end of the Polyponnesian War. Since Athens lost it, it ceased to be a stabilizing power at sea. The marauding bands on land and at sea run through the sources of the fourth century, Plato's time. Often these were groups of violent actors who also served as mercenaries in the meantime. Whereas in the fifth century, most Greek soldiers were citizens, mercenaries now played a far greater role. Specialized, but serving whoever paid and not necessarily beholden to their city. Politicians in Athens in particular saw this with horror. The fluid boundaries between state violence and brigandage observed by Augustine's pirate is once again evident. In the absence of a client or other income, the mercenaries earned their money on their own account. Wherever there was a lack of defenses, one was therefore threatened by pirates or brigands, especially on the coast. The fragmented political situation in the Aegean did not allow for a common defense, especially since the problem was interpreted as a moral, not a structural one. The Persian Empire, on the other hand, seems to have ensured tranquility in its sphere of power, the Eastern Mediterranean. The fact that mercenaries and piracy or banditry were so intertwined in the Aegean and adjacent waters seems to have shaped the maritime history of the period. The military practice of the pirates was thus professionalized. They were noble, they were mobile communities of violence that generated their income in different ways, partly in the service of recognized political authority, partly on their own. With the empire of Alexander the Great, the possibility of a unified rule in the entire Aegean and the Eastern Mediterranean was in the offing, but it proved to be short-lived, as did its successors, the Daedokai. These struggled with each other for supremacy. The Ptolemies in particular, whose basis of rule was that Egypt claimed a thalassocracy, a rule over the sea. In the third century, they actually had bases and entire territories on opposite coasts in the Aegean, in Asia Minor, and in the Levant, but they gradually forfeited them. The aim of their opponents was to wrest the thalassocracy from them, or at least to reduce it, which they actually succeeded in doing. This meant, on the other hand, destabilizing the sea, especially as the warring parties were happy to deploy troops or seek allies who polemically called their opponents pirates. It is difficult to say what was behind this in individual cases. These violent entrepreneurs could have been similar to the groups that later received letters of mark, but they could also have existed in the already mentioned alternation between mercenary status and independent communities of violence. The travelers, but also many coastal towns, lived in constant fear of the pirates. The sea was already dangerous due to storms. Shipwreck was a serious risk, and now the pirates were at it. If the risk of the sea spoke in favor of coastal shipping, it was precisely the proximity of the coast that was threatening, as pirates could more easily reach the ships from their loopholes. The wars are attested not only by literary texts, but also by stone inscriptions on which cities recorded resolutions, permanently documenting their measures against pirates or unarmed men who fought the pirates. Even those who had only communicated. The arrival of pirates could earn praise to be inscribed on stone. It was precisely the competition between the empires that opened up scope for action for the pirates, as they had many opportunities to hire themselves out as mercenaries. In fact, that the Romans had been gaining power in the Eastern Mediterranean since the second century BC did not stabilize the situation. On the contrary, Roman policy further strengthened piracy. In 188 BC, the Romans forced the Seleucid king Antiochus III the Great to give up his rule over Asia Minor, west of the Taurus, and a large part of his fleet after his defeat in the so-called Peace of Apamea, but did not establish stable structures on the southern coast. This further strengthened the pirates. Rome also weakened the idend state of Rhodes, which together with its allies had successfully fought the pirates in the Aegean. Rome instead made Delos, which could not defend itself, let alone fight pirates, a free port. In the beginning, the Romans obviously had no interest in the stable eastern half of the Mediterranean. Be it that this area was not important enough for them, be it that they even wanted to prevent stable structures, pirates would have been extremely useful here, an unholy and probably also unspoken alliance. Just in the period after Alexander the Great, as mentioned, the word parates, which usually refers specifically to pirates, also appeared and spread rapidly. In literature, pirates now also play a greater role, interestingly enough, especially in comedies and novels. For the fact that people are captured by pirates leads to siblings, lovers, parents, and children being torn apart and reunited in complicated ways, accompanied by adventures, many misunderstandings, and mixed ups appeal to many readers. What does not exist in literature, as far as I can see, is the type of pirate as a romantic hero. Nor does there seem to be an artistic pirate stereotype, as we know it from later. A much feared experience was the role reversal it meant when a nobleman, even a powerful Roman, fell into the hands of pirates. When someone claimed to be a distinguished Roman, they paid him respect, dressed him in Roman clothes, and forced him to climb a ladder down into the sea to drown while taunting him, Plutarch reports. The young Julius Caesar also fell into the hands of pirates around 70 BC. Later tradition praises his condescending handling of them. He raised the ransom because the 20 talents they demanded for him was too little for someone like him. Moreover, he forced them to follow his pyrhythm, read them his literary works, and called them barbarians if the applause did not erupt violently enough. The presence of the pirates therefore endangered all travelers, especially the nobles, since they were attractive victims. Freed again, Caesar was able to overpower the pirates by gathering enough Roman ships and had them all killed by crucifixion, which he mitigated by cutting their throats first. Now order was restored to a certain degree. But the very glowing reports of its show what a humiliation pirate kidnapping was, and Caesar had not found a lasting solution, for pirates continued to terrorize the Eastern Mediterranean. The fact that pirates were able to operate so successfully was not only due to external factors, but also to a change in the structure of piracy. Certainly, there continued to be occasional pirates, such as the fictional Odysseus. Certainly, there continued to be communities of violence that sometimes are referred to as mercenaries, sometimes as pirates, but stable. Largely autonomous forms of pirate organizations can now also be observed. Significantly, the idea also emerged that there had to be a common war of Greeks against pirates, but it was difficult to realize unless a power such as Rhodes at times took charge of it. The epitome of the development towards a pirate empire are the Cilician pirates, with their center in Corochesion in southern Anatolia. Those who had captured Caesar and on whom he took revenge without being able to destroy them altogether were also among them. They are attested since the second century in Cilicia, mainly in Cilicia. This was the region that was removed from the control of larger empires by Rome's policy. The lands were situated in regions close to the sea, separated by ranges of hills similar to the Mani, and therefore lend themselves to asymmetrical warfare. The great powers obviously shied away from the expense of a siege. In addition, these regions were not very fertile so that they did not seem suitable for a self-sustaining buildup of power based only on peaceful trade. This is why they had hardly been settled before and were not attractive for conquerors. An alternative to piracy was therefore difficult to develop for the people living there. The pirates were strengthened once again by the fact that they were able to take over the fleet of a Syrian pretender to the throne named Trifon, who had committed suicide when his hopes were dashed. Once again, the unsurprisingly fluid transition from mercenaries to piracy is evident. After all, the pirates' power was based on the fact that they provided a sought-after commodity, slaves. As otherwise the Romans had to rely mainly on wars to obtain slaves, making the supply very uneven, the pirates continuously supplied their goods and sold them unmolested at recognized international trading centers such as the aforementioned Delos, but also at Cede in the Cilician homeland. They called themselves slave traders instead of pirates, complains one ancient author. The demand and the increasingly wealth the Roman society was apparently steady and made the pirates rich. At their height, the Cedician pirates are said to have owned more than a thousand ships and captured more than 400 cities. Such figures should always be taken with caution. However, they used some cities as bases on various coasts, not only in Cilicia, but also in Crete, the Aegean, and even the Balearic Islands. Some pirates ruled over several towns and perhaps also in the hinterland. They acted like local potentates. So according to the definition of pirates quoted by Augustine, there would not have been pirates at all. With their excellent logistics and fast ships, they were difficult to capture militarily, especially since they also set sail in stormy winter. They felt powerful enough to occasionally venture inland and even sailed into the port of Ostia, which supplied Rome. Sartorius, who rebelled against senatorial rule in Spain, also allied himself with pirates and attacked Ibiza together with them. Even Spartacus, the king of the slaves, is said to have supported them. The disruptive potential of the pirates no longer affected the Hellenistic empires alone, which no longer deserved the name empire anyway, but also Rome itself, even into the far west. The internal cohesion of the pirates was considered to be great, but we do not know much about the institutions. The privates obviously had families, so they assumed that they could settle down permanently. They were on the way to regular statehood, had their own ideas of honor, and were useful allies. The pirates' lifestyle irritated the Roman authors, who certainly emphasized the abnormal, such as the gold-plated masts and purple sails. Purple was the color of royalty. Furthermore, the imperial historian Appian indignantly reports an idea of their self-portrayal. The commanders would have called themselves Strategoi. They would have rejected the designation as Lestai robbers and described their booty as soldiers' wages. They would have had specialized craftsmen for shipbuilding and would have called their leaders kings. They would also have established signal stations between their cities and bases. They were on the way to regular statehood, had their own ideas of honor, and were sought after allies. Plutarch even speaks of the fact that rich and noble people would have joined because they could gain fame that way. This is reminiscent of Thucydides and shows that the archaic model of honorable piracy was still alive. The pirates, we hear, defied what was considered sacred among Greeks. They plundered common Greek sanctuaries, such as Epidaurus or Didyma, and maintained their own cult center that specialized in Olympus in Southern Anatolia, not the famous Olympus in Greece, where they would have worshiped Mithras among others. The cult for the originally Iranian god, as we know it from later times, supported a pronounced ideal of masculinity which would fit this group. Since religion and policy were inextricably linked, the cult did not simply signify a pious idiosyncrasy, but formed an element of statehood, of nascent statehood. Of course, one must again take such statements with a grain of salt. For the passages from Plutarch that give this information, a primary intended to celebrate the outstanding achievements and royal qualities of Pompey, the later pirate conqueror. Yet the title of king for a pirate leader is even attested epigraphically in a documentary source, an inscription on a consecration in the common Greek sanctuary, Panhellenic sanctuary of Zeus at Dodona, where then one obviously sought recognition after all and respected a great Panhellenic Greek sanctuary. The Romans must have been shocked when their obstinate enemy, Mithridates, the sixth Eupator, legitimate king in North Asia miners Bithynia and Pontus, resorted to pirates and allowed himself to be transported by a pirate ship when his fleet was largely destroyed by a storm. He arrived at his residence safe and sound. But this also means that Mithridates, albeit in an emergency situation, acknowledged this group and treated them as equals, as it were, which was only wise, for the Romans suffered far more damage from them than his subjects and allies. In general, Mithridates' wars with Rome increased the pirates' scope for action, even if he eventually lost against Rome. This pirate empire was thus on the way to normalization and seemed to confirm Augustine's dictum about the proximity of piracy and statehood. From the Roman point of view, however, these people meanwhile were dangerous pirates, the more so as they meanwhile severely disrupted the development of trade, especially in a central area. Similar to Athens, the political field was endangered where ancient powers were most inclined to pursue a targeted economic policy, that of grain supply. It had also been mentioned that the pirates had penetrated as far as Ostia where the grain was unloaded. In addition, there was the personal danger of many Romans, especially many noble Romans. Several times since the end of the second century, Romans tried to intervene directly or by forbidding others to harboring pirates. They were usually successful if it came to a military confrontation with pirates like Caesar's, but the pirates always found places to retreat from which they could continue their activities in a kind of maritime partisan tactic. As with Caesar and the longstanding conflict with Eastern kings aggravated the situation. It was not until Pompey, Caesar's later rival, defeated the pirates with a coordinated enterprise in 67 BC. As he approached them, an idolizing source says, the first ones surrendered whom he spared and took in with their families. They revealed to him the hiding places of the others, which he could easily conquer. At their center, Caucasion, he defeated them in a sea battle. At the same time, he offered them a perspective. He settled the survivors in cities. And from them on, they practiced agriculture here. Hooks became plowshares to put it rather flippantly. However, many pirates were apparently also incorporated into the Roman army where they could legitimately continue their activities and were under control. But this was a continuation of older traditions of switching between piracy and mercenaryism. This makes Pompey's famous success perhaps less extraordinary. The triumph was only possible because Pompey was granted extraordinary special rights and enormous military resources by the Roman people. Thanks to this success, he received additional powers and resources and set out further ease to bring Asia Minor and Syria fully under Roman rule. This, too, contributed to the lasting success. Apparently, the control of territory, which Rome had long avoided, made it easier to overcome the pirates. The success was lasting for contemporaries as well as for later generations, even if pirates continued to appear sporadically. The rapid victory also shows that the pirates were sham giants. But perhaps it was precisely the increasing formation of state-like structures that contributed to their downfall. For this made them a more predictable opponent for Rome, which had not been able to cope with partisan tactics. But this would be a matter of debate. Perhaps Rome proved to be the stabilizing power that the Diadochi had been unable to be after Alexander the Great, and Pompey succeeded the Hellenistic kings that proved incapable of suppressing the pirates. Rome's ability to keep the peace may also have impressed local elites who depended on safe sea routes. These special powers and successes might already have enabled the establishment of monarchical order, but Pompey did not let himself be carried away by this. He had, however, shown by the example of the fight against the pirates what efficiency a Roman in doubt, without sending rights, was capable of. The classical drama, to conclude, the classic drama by the Frankfurt born German poet Johann Wolfgang von Goethe-Faust contains a much quoted sentence in its second part. Handel, Krieg und Piraterie, drei einig sind sie nicht zu trennen. Trade, war and piracy, they are three of a kind, not to be separated. This sentence certainly applies to large parts of the history of piracy. The transition from piracy to regular trade and especially to mercenarism was often fluid, especially when cross-cultural political systems such as those of the ancient world had no regulatory authority recognized by all sides that could enforce a binding definition of piracy. As it seems, it was not until a polis like Athens gained power over a part of the sea, the Aegean, that the concept of piracy gained currency. And even later, the technical term came into being that distinguished pirates from other robbers. The word does not occur as a self-designation, however, for obvious reasons. Nevertheless, despite the difficulty of demarcation in specific cases, there were common ideas about what piracy was and what the corresponding polemic meant when it was applied fairly or not. It was violence at sea that was based on robbery and kidnapping, not on permanent conquest, and that was not honorable. It was not done in the service of a polis or recognized power, although this vague expression again indicates a problem. The communities of violence could exercise violence on their own, but also in the service of other powers, and then resembled mercenaries. Then, in modern research, they are not called pirates, but mercenaries. The idea of piracy was clearly contoured, but the phenomenon of piracy was difficult to delineate. The history of piracy in the Greek world, up to the time of Pompey, shows that pirates profited from the interstices between great powers and from the existence of mobile communities of violence, which resulted from the fact that the permanent maintenance of soldiers was expensive unless they could be used in war and could fall back on duty. Three forms of piracy can be observed. They developed in different phases of Greek history, but did not replace each other. First, occasional piracy, which the Odyssey presupposes, in which was not considered illegitimate, in some cases even honorable. Groups such as Odysseus' companions returning from Troy could, in their literary accounts, seize an opportunity to raid an unfortified city, but had to give way to the combined forces of the land dwellers. The second stage was the link between mercenarism and piracy, in the wake of the Peloponnesian War, whereby the same group could act as mercenaries and as pirates on occasion. This favored a professionalization of fighting techniques and meant that the pirates posed an even greater danger. Of course, there were also mercenaries who continued to operate as brigands on land, but the mobile pirates were more elusive than ordinary razors, who remained in one zone so that an operation was more likely to be worthwhile, and a captured ship promised more beauty than merchants traveling on land. However, piracy required a large initial investment in the form of a ship and training. Eventually, the Cilician pirate empire developed, which was close to a normal state. In a way, one could portray the history of piracy as that of an unfinished normalization. However, from the point of view of the Roman Empire, which now dominated the eastern Mediterranean world, it was so disruptive that Pompey destroyed it in a sweeping action. In fact, decades of relative calm set in. Only the Vandals were to cause great unrest, again in the 5th century AD. For some, the Vandals formed a kingdom. For others, they were a pirate community. And in this respect, Augustine's pirate was proven right once again. Thank you for attention and good night.